Cavotricuspid isthmus ablation for atrial flutter guided by contact force related parameters: A systematic review and meta-analysis - Pang, Naidong; Gao, Jia; Zhang, Nan; Guo, Min; Wang, Rui (Frontiers in Cardiovascular Medicine, 2023)
Background: Contact force (CF) and related parameters have been evaluated as an effective guide mark for pulmonary vein isolation, yet not for linear ablation of the cavotricuspid isthmus (CTI) dependent atrial flutter (AFL). We thus studied the efficacy and safety of CF related parameter-guided ablation for CTI-AFL. Methods: Systematic search was performed on databases involving PubMed, EMbase, Cochrane Library and Web of Science (through July 2022). Original articles comparing CF related parameter-guided ablation and conventional parameter-guided ablation for CTI-AFL were included. One-by-one elimination, subgroup analysis and meta-regression were used for heterogeneity test between studies. Results: Ten studies reporting on 761 patients were identified after screening with inclusion and exclusion criteria. Radiofrequency (RF) duration was significantly shorter in CF related parameter-guided group (p=0.01), while procedural time (p=0.13) and fluoroscopy time (p=0.07) were no significant difference between two groups. CF related parameter-guided group had less RF lesions (p=0.0003) and greater CF of catheter-tissue (p=0.0002). Touch-up needed after first ablation line was less in CF related parameter-guided group (p=0.004). In addition, there were no statistical significance between two groups on acute conduction recovery rates (p=0.25), recurrence rates (p=0.92), and complication rates (p=0.80). Meta-regression analysis revealed no specific covariate as an influencing factor for above results (p>0.10). Conclusions: CF related parameters guidance improves the efficiency of CTI ablation, with the better catheter-tissue contact, the lower RF duration and the comparable safety as compared with conventional method but does not improve the acute success rate and long-term outcome.